2020
DOI: 10.1101/2020.05.26.20109595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and harms of remdesivir for the treatment of COVID-19: a systematic review and meta-analysis

Abstract: Background: We evaluated the efficacy and safety of remdesivir for the treatment of COVID-19. Methods: Systematic review in five engines, pre-print webpages and RCT registries until May 22, 2020 for randomized controlled trials (RCTs) and observational studies evaluating remdesivir on confirmed, COVID-19 adults with pneumonia and/or respiratory insufficiency. Primary outcomes were all-cause mortality, clinical improvement or recovery, need for invasive ventilation, and serious adverse events (SAE). Secondary o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Additionally, Liu et al found in their SR and metanalyses that there was insufficient evidence that suggests any benefit from the treatments included (Lopinavir/Ritonavir, Ribavirin, Chloroquine, hydroxychloroquine, arbidol, favipiravir) in the clinical outcomes of the patients. Also, they found an increase in the GI adverse events with the use of Lopinavir/ritonavir [18].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Liu et al found in their SR and metanalyses that there was insufficient evidence that suggests any benefit from the treatments included (Lopinavir/Ritonavir, Ribavirin, Chloroquine, hydroxychloroquine, arbidol, favipiravir) in the clinical outcomes of the patients. Also, they found an increase in the GI adverse events with the use of Lopinavir/ritonavir [18].…”
Section: Discussionmentioning
confidence: 99%
“…Remdesivir has been shown to inhibit SARS‐CoV‐2 replication in human stem cell‐derived intestinal organoids 279 . This potent in vitro activity against SARS‐CoV‐2 has led to a number of clinical trials of intravenous remdesivir in adults hospitalized with COVID‐19 280–287 …”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%
“…The data from 1075 patients with COVID‐19 demonstrated that patients receiving remdesivir had a higher discharge rate (50.43% vs. 45.29%) and a lower mortality rate (8.2% vs. 12.7%) than patients in the placebo group 285 . Another similar study analyzed two randomized controlled trials ( n = 1300) and two observational studies ( n = 88) in which remdesivir 200 mg IV was given on the first day and 100 mg IV was given daily for 9 more days 286 . Remdesivir decreased the median time to recovery in one randomized controlled study but did not decrease the time to clinical treatment in the other randomized controlled study 286 .…”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%
See 1 more Smart Citation
“…Other systematic reviews found an increase in the risk of diarrhoea and nausea and/or vomiting with lopinavir-ritonavir 37,38 and hydroxychloroquine, [38][39][40] increase in arrhythmias and QTc interval prolongation with hydroxychloroquine alone, [40][41][42] or combined with a macrolide, 43,44 and no significant increase in renal failure with remdesivir. 45…”
Section: Strengths and Limitations Of This Reviewmentioning
confidence: 99%